Crosslinguistic influence in the written English of Malay undergraduates - Azirah Hashim (Journal of Modern Languages)
The purpose of this paper is to describe, analyse and explain the cross linguistic influence in the written English essays of Malay undergraduates to determine how similarities and differences between English and Malay can influence the acquisition of English and also to look at how the students' own culture influences the written work of these students. The term 'cross linguistic influence' is commonly known as language transfer which has been defined as 'the influence of the mother tongue on the learner's performance in and/or development of a given target language' (Sharwood Smith, 1994: 198). It also includes the influence of any other language known to the learner prior to learning the target language. For a thorough understanding of transfer, it is necessary to make structural comparisons but also to take into account non-structural factors such as the cultural beliefs and values of the writers..